Petrologia do stock Serra da Vaca, domínio Poço Redondo, sistema orogênico sergipano - Oliveira, Douglas Barreto de (2019)
The Serra da Vaca Stock (SSV), with 19 km2 area, is NE-SW elongated been and is located in the Poço Redondo Domain, in the Sergipano Orogenic System. The SSV intrudes in the Poço Redondo migmatites and in the granites of batholith Poço Redondo. The SSV is constituted by biotite granodiorites, with alkali-granite and syenogranites subordinate. The SSV rocks have gray color, isotropic dominant structure and equant texture. The essential mineralogy of these rocks is composed of plagioclase, microcline and quartz. Accessory phases are epidote, zircon, apatite and opaque minerals. Plagioclase presents normal zonation, indicative of fractional crystallization and its compositions vary from albite, in the most evolved rocks, to andesine, in the less evolved. The alkali feldspars are pertythitic and the shows compositions close to the pure poles of albite and orthoclase. The biotite is the principal mafic phase in the rocks and has Fe/(Fe + Mg) ratio ranging from 0.47-0.84 and AlTot of 2.859-3.927 atoms per unit formula. These compositions indicate that the biotite crystals are primary and primary reequilibrated which crystallized from a calc-alkaline magma. The presence of primary epidote (19.9<%Ps<28.85) indicates oxidizing crystallization conditions and the minimum pressure of 5 kb (~ 25 km). Geochemical data indicates that SSV rocks are strongly evolved (70%<SiO2<77,5%), peraluminous and magnesian. The magmatic affiliation of the granodiorites is high K calc-alkaline, whereas the most evolved terms present shoshonitic affinity. The chemical data of major elements suggest that SSV magma formed from the fusion of igneous protoliths. The ratio of granodiorites and alkali-granite indicates strong fractionation 11<(La / Yb)N <70. Eu anomalies are not pronounced for most of the SSV samples (0,57< Eu/Eu * <0,97), except for alkali-granite and syenogranites, that exhibits strong negative anomalies (0.16-0.30). The relationships between trace elements (Th, Ta, Hf, Y, Nb, Rb) indicate that the Serra da Vaca Stock rocks were formed in an orogenic environment and a post-collision period.